2021
DOI: 10.3389/fcell.2021.683940
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress and Tumor Microenvironment in Bladder Cancer: The Missing Link

Abstract: Bladder cancer is a common malignant tumor of the urinary system. Despite recent advances in treatments such as local or systemic immunotherapy, chemotherapy, and radiotherapy, the high metastasis and recurrence rates, especially in muscle-invasive bladder cancer (MIBC), have led to the evaluation of more targeted and personalized approaches. A fundamental understanding of the tumorigenesis of bladder cancer along with the development of therapeutics to target processes and pathways implicated in bladder cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 178 publications
(189 reference statements)
2
23
0
Order By: Relevance
“…CRT silencing inhibited ERS-induced cell mobility and chemoresistance via promoting autophagy in vitro ERS, as a series of adaptive changes mediated by UPR, takes part in cancer development via mediated tumor malignant behavior (proliferation, migration, apoptosis and survival) and autophagy [22,23]. In current study, transwell assays rst showed that TG signi cantly induced cell invasion and migration in Capan-2, Miapaca-2 and Panc02 cells (Fig.…”
Section: Crt Silencing Inhibited Ers-induced Autophagy In Pc Cellssupporting
confidence: 55%
“…CRT silencing inhibited ERS-induced cell mobility and chemoresistance via promoting autophagy in vitro ERS, as a series of adaptive changes mediated by UPR, takes part in cancer development via mediated tumor malignant behavior (proliferation, migration, apoptosis and survival) and autophagy [22,23]. In current study, transwell assays rst showed that TG signi cantly induced cell invasion and migration in Capan-2, Miapaca-2 and Panc02 cells (Fig.…”
Section: Crt Silencing Inhibited Ers-induced Autophagy In Pc Cellssupporting
confidence: 55%
“…Activation of UPR results in a decrease in the number of proteins synthesized and an increase in the extent of protein folding realized. These are achieved by regulating the UPR-related gene expression and pathways ( Nie et al, 2021 ). It has been previously reported that ER stress affects multiple aspects of cancer ( So, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an increasing number of chemotherapy resistance mechanisms involved in ER stress have been discovered. ER stress-related molecular markers, such as GRP78, PERK, IRE1α, have been reported to have prognostic values for cancer patients [124].…”
Section: Erlins: New Actors In the Crosstalk Between Autophagy And Apoptosis In The Cancermentioning
confidence: 99%
“…Since aberrant UPR and ER stress are major contributors to cancer development, chemoresistance, and poor prognosis, there has been strong interest in clinically influencing this process as a strategy to restrain tumor growth and reverse drug resistance. Overall, generation of high-quality small molecules to modulate ER stress or to target the UPR, either as a monotherapy or in combination with chemotherapy, targeted therapy, and immunotherapy have shown promising preclinical treatment efficacy and offering the opportunity to develop therapeutics for a vast range of ER stress-related diseases [124,125].…”
Section: Erlins: New Actors In the Crosstalk Between Autophagy And Apoptosis In The Cancermentioning
confidence: 99%